NEED FOR INNOVATION IN GRILLED FISH PRODUCTION OF FARMERS IN VILLAGE 1, KHOK SAMRONG SUB - DISTRICT, KHOK SAMRONG DISTRICT, LOPBURI PROVINCE - Yencham, Chayaporn; Rengkounkway, Metta; Samngamya, Preeda; Chumjai, Praderm (Journal of MCU Nakhondhat, 2023)
The purposes of this research were to study 1) Personal basic economic and social factors 2) Supporting Factors 3) Motivation factor 4) Needs for innovation in grilled fish production and 5) Relationships between personal basic economic and social factors, supporting factors, and motivation factors, and needs for innovation in grilled fish production of farmers. The population used in the study were 203 farmers in Moo 1, Khok Samrong Sub - district, Khok Samrong District, Lopburi Province and 133 of them were chosen as the study samples. Data were collected using questionnaires and analyzed by using descriptive statistics including frequency, percentage, mean, standard deviation, maximum and minimum values and inferential statistics which was Chi - square. The study results showed that 1) Most of the farmers were female at 62.4%, average age was 54.93 years old, completed primary school educational level at 82.0%, average income was 71,837.60 baht/year. The average expenditure was 18,009.02 baht/year. The average experience in making grilled fish was 29.77 years. Participation in the agricultural group of the village fund group was at 53.4%. 2) Most of the farmers had a channel to receive information from their neighbors at 93.7% and the source of funds for farmers was the most from their own at 100.0%. 3) Farmers had the highest level of motivation factor, the need for success, 2.39, followed by the need for commitment, 2.38, and the need for power, 2.33. 4) Farmers had the highest level of need for innovation in terms of inputs with an average of 2.37, followed by production processes with an average of 2.35, productivity with an average of 2.34 and marketing with an average of 2.31. 5) The hypothesis testing results showed that age, education level, income, experience in grilled fish production, need for success, need for relationship and need for power were related to the overall aspect and individual aspect of need for innovation at 0.05 level of significant.